2008
DOI: 10.1111/j.1365-2486.2008.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the effects of free‐air CO2 enrichment (FACE) on growth, morphology and physiology of rice root at three levels of nitrogen fertilization

Abstract: Over time, the relative effects of elevated [CO 2 ] on the aboveground photosynthesis, growth and development of rice (Oryza sativa L.) are likely to be changed with increasing duration of CO 2 exposure, but the resultant effects on rice belowground responses remain to be evaluated. To investigate the impacts of elevated [CO 2 ] on seasonal changes in root growth, morphology and physiology of rice, a free-air CO 2 enrichment (FACE) experiment was performed at Wuxi, Jiangsu, China, in 2002-2003. A japonica cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 27 publications
3
55
0
2
Order By: Relevance
“…However, to take full advantages of the CO2 fertilization effect, management of soil N availability has been shown to be very crucial [4][5][6][7] . Urea is the most extensively used fertilizer (accounted for 40% of total synthetic fertilizer consumption in the world), and is very susceptible to loss particularly via ammonia volatilization 8) .…”
Section: Introductionmentioning
confidence: 99%
“…However, to take full advantages of the CO2 fertilization effect, management of soil N availability has been shown to be very crucial [4][5][6][7] . Urea is the most extensively used fertilizer (accounted for 40% of total synthetic fertilizer consumption in the world), and is very susceptible to loss particularly via ammonia volatilization 8) .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we did not obtain an accurate count of the roots due to the huge roots number. Yang demonstrated that under elevated [CO 2 ], the increase of the number of adventitious roots, and the root volume and root dry weight per plant were similar (about 30%) at 80 days after transplanting [17]. The findings suggested that under elevated [CO 2 ], the increase in root biomass was mainly attributable to an increase in root number.…”
Section: Discussionmentioning
confidence: 62%
“…Studies confirmed that during rice growth, after stem lodging, root lodging is the next greatest lodging risk, and also proved that the larger roots system and thicker crown roots in subsoil were the very important characteristics for anti-lodging for root [15,16]. Although most studies approved that elevated [CO 2 ] promoted root growth, and increased the root volume, root biomass of rice [17,18], no study has examined the risk of root lodging under elevated [CO 2 ].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The parameters, such as volume, TSA (total root surface area), AAA (active absorption area), and AAA/TSA of roots were are considered to be crucial in root function (Yang et al 2008). The present study provides clear experimental evidence which states that all the four parameters in Downwind sites were significantly lower than those values obtained in Upwind sites.…”
Section: Water Hyacinthmentioning
confidence: 99%